An Analysis of Flouting of Maxim in Aiman’s Talkshow ‘Tudingan Konspirasi Di Balik Korona’ - Bayu Andika Prasatyo; Yayu Kurniyawati (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The aims of this study are to investigate the flouting of maxim and analyse the implicature of it. To interpret and analyze the data, the research applied a descriptive qualitative method. The data were the utterances produced by Aiman Wicaksono as the Interviewer and Jerynx SID as the Main Guest speaker. The researchers conducted the analysis by identifying the data applying Grice’s Cooperative Principle (1975), categorizing the flouting of maxims as well as investigating the most dominant maxim of floating which occurred in Aiman’s talkshow video. The result of the finding shows that the guest speaker flouted all maxims. The maxim flouted when the speaker responded irrelevant statements, answered to the question but lack of adequate evidence, said too much and or too little information than it is required, and replied something unclear or ambiguous as well as provided unnecessary prolixity. The study discovers that there are 6 occurrences of flouting the maxim of relevance, 4 occurrences of flouting the maxim of manner, 1 occurrence of flouting the maxim of quantity, and 1 occurrence of flouting the maxim of quality. It is found in the research that the most dominant occurrence of flouting maxim is maxim of relevance. It is indicated by the contributions provided by the guest speaker where he does not make the contributions relevant to the questions and context.